PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD PADA MATA PELAJARAN BAHASA INDONESIA MATERI PERASAAN PADA KELAS II SDN MANGKANG KULON 01 - Sekar Ayu Rachmawati; Mudzanatun; Kartinah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the limited availability of Indonesian language learning media on the topic of emotions in Grade II at SDN Mangkang Kulon 01. The aim was to assess the validity, practicality, and responses to the use of flashcard learning media, with the Research and Development (R&D) method with the ADDIE model and involving 14 grade II students. Data were obtained through questionnaires, interviews and documentation, which were then analyzed using qualitative descriptive methods. Material validation scored 95% and media validation 94.5%, both categorized as very feasible. Student worksheet practicality reached 97.1% and categorized as very practical, teacher responses 90%, and student responses 95.3%, all rated as very good. The flashcard media was found to be valid, practical, and positively received, effectively increasing student engagement. It is recommended to use such media to help students understand emotions and to encourage teacher creativity in designing enjoyable and effective learning experiences.